An Economic Analysis of Government Financing for Development in Malaysia - Abdul Aziz, Mariam (1993)
This study examines the ways and means of government spending and the consequent impacts on the economy . The scope for enhancing the efficiency of government spending and the utilisation of the various sources of revenue are identified so as to maximise the net benefit of government involvement in the economy. The main sources of financing government expenditure include taxes, domestic and foreign borrowing and credit creation. Trends of both the spending and financing aspects of the government budget are also discussed within the context of several related theoretical and empirical debates. Initially, the level of analysis is partial in nature, using single equation estimates, although cross references are made to link the various sources of government financing and spending. A simple macroeconomic model within the context of a simultaneous equation system is later developed to identify the impact of changes in several sources of government finance on main macro variables such as GNP, employment, prices, wages and private investment. This is done through several simulation exercises involving changes in policy variables such as taxes, the supply of money and public borrowing.